Transtornos mentais comuns, qualidade e satisfação na vida de mulheres profissionais do sexo - Elias, Ana Rosa Ribeiro (2017)
This study aimed to assess mental health indicators (common mental disorders, life quality, satisfaction with life), among female sex professionals, who work at brothels in Uberlândia (MG). A cross-sectional, exploratory, quantitative study was conducted with 158 female sex professionals. Satisfaction with Life Scale (SWLS), WHOQOL-BREF (about life quality), Self Report Questionnaire (SQR-20) and sociodemographic information were used to collect data. Level of significance (p value) was set at 0.05 for all variables. Descriptive analysis of data in absolute and relative frequency were performed. Quantitative variables were described through mean, median, maximum and minimum standard deviation. Shapiro-Wilk Test also was applied. For variables that presented and followed normal distribution, One-way ANOVA was applied to compare groups. Kruskall-Wallis Test was applied for quantitative variables that did not follow normal distribution. Pearson Correlation Coefficient was used to evaluate the association between quantitative variables, in addition to G-test (likelihood-ratio). About qualitative variables, they were described using a SPSS v.20 software. This research showed the majority of female sex professionals had declared to be single (75.9%), from pardo or brown ethinic group (51.9%), literate (99.4%), and living in a rented house (58.2%). For WHOQOL-BREF domains, domain 1 – Physical Health presented statistical relevance (p=0.00495) and level of satisfaction with an average score of 66.48 (dp±16.02). Concerning about the SWLS, 46.5% of the women (N=73) had answered if they could have a new beginning, they would take different attitudes and choices in life, which corresponds to the number 1 of the SWLS (strongly disagree). In this study, a relation between ethnicity (p=0.0301) and type of housing (p=0.0046) with the statement "If I could live my life over, I would change almost nothing" (SWLS) was detected. Common mental disorder symptoms were identified in 51.6% of female sex professionals. There was an association of domain 1 - Physical Health (WHOQOL-BREF) with level of education (p=0.0207), and years of study (p=0.0027). A significant statistical correlation between family income and domain 1 - Physical Health (p=0.0133) and domain 4 - Environment (p=0.0009) was also detected. It was concluded that female sex professionals present mental disorders symptoms, associated with low levels of quality and satisfaction with life, similar to those of population at large. The literature about level of common mental disorders symptoms, quality and life satisfaction, and its correlations among female sex professionals is limited and requires further investigation. This survey also highlight the need for more egalitarian public policies and skilled health professionals to assist those women.